LOAN MANAGEMENT AND FINANCIAL PERFORMANCE IN FINANCIAL INSTITUTIONS: A CASE STUDY OF BANK OF KIGALI GISENYI BRANCH (BK)(2019-2021) - Joseph, Bizimungu; Isaï Kadhafi, Dr. MISAGO; Byamukama Mpora, Eliab; Frank, HAGUMIMANA (International Journal of Scientific Research and Management (IJSRM), 2023)
This study examined the effect of loan management on the financial performance of commercial banks in Rwanda. Banking sectors play a key role within the development of an economy. The development role the steadiness of banking sector determines the step for development of economy. Hence the steadiness of banking sector may be a key for the event of an economy. Descriptive case study design is used since it allows to the researcher to find information about the present status of a phenomenon to describe “what exist” with respect to variables or conditions in a situation (Yin, 2003). The study considered 20 respondents as sample size. A correlation coefficient measures the strength and direction of a linear association between two. A correlation coefficient measures the strength and direction of a linear association between two variables. It ranges from -1 to1. The closer the absolute value is to 1, the stronger the relationship. BK should reduce all those process of getting loans and help their clients who requesting for loans to get them in few days, this will help the bank to provide many loans and get profit from it.